Batasan dan Ruang Lingkup Rumah Sakit Pendidikan - Supriyatiningsih, - (Universitas Muhammadiyah Yogyakarta, 2002)
In Indonesia, Teaching Hospital and Medical School are two separate institutions whereas each of them has its own organizational structure and bylaw. Teaching Hospital is a hospital which also functions as an official centre for education and training for health personnel trainees i.e. medical doctors, nurses, midwifes, others. The prerequisite for a hospital to be utilized as an education and training center is to fulfill some criteria; one of them is the accreditation status as a teaching hospital which is issued by the profesÂsional organization. However, the Joint Decree by 3 Ministers which regulates the scope of teaching hospital requires to be re-evaluated.Â Di Indonesia Rumah Sakit Pendidikan dan Fakultas Kedokteran merupakan 2 institusi yang terpisah dimana masing-masing memiliki struktur organisasi dan landasan hukum sendiri-sendiri. Rumah sakit Pendidikan adalah rumah sakit yang juga berfungsi sebagai pusat resmi untuk belajar bagi pendidikan atau pelatihan dokter, perawat dan tenaga kesehatan. Suatu Rumah Sakit agar dapat digunakan sebagai tempat pendidikan, maka diharapkan agar dapat memenuhi beberapa criteria antara lain terakreditasi sebagai ruah sakit pendidikan yang dikeluarkan oleh organisasi profesi. Surat Keputusan Bersama 3 Menteri yang mengatur batasan Rumah Sakit Pendidikan perlu dikaji ulang.